Molecular-Kinetic Approach to Gas-Flow Problems. Issue 5 (October 2013) - Tsukamoto, M.; Sakurai, A.
The primary aim of this paper is to analyze the feasibility of the molecular kinetic approach to problems with computation of compressible flows. We present the Boltzmann equation methods and its application to various gas-flow problems.